Children in Colonial America. - Marten, James (Children and youth in America., 2006)
The Pilgrims and Puritans did not arrive on the shores of New England alone. Nor did African men and women, brought to the Americas as slaves. Though it would be hard to tell from the historical record, European colonists and African slaves had children, as did the indigenous families whom they encountered, and those children's life experiences enrich and complicate our understanding of colonial America. Through essays, primary documents, and contemporary illustrations, Children in Colonial America examines the unique aspects of childhood in the American colonies between the late sixteenth a.